Studi Kasus: Penatalaksanaan Terapi Milieu Untuk Meningkatkan Keterampilan Sosial Pada Pasien Demensia - Tiara Shafa Azhara (Yayasan Healing and Healthcare Education, 2023)
Social skills are efforts to improve a person's ability to express what is needed and wanted, to be able to refuse and convey a problem, to be able to respond when interacting socially, to be able to initiate interactions, and to be able to maintain interactions that have been built. The research objective was to improve social skills in dementia patients by being given milieu therapy. Research methods used qualitative methods and interviews were conducted using psychogerontic assessment. The research was conducted using interviews and using the Mini Mental Status Exam (MMSE) rating scale on 2 elderly people for 4 days. The results of the study show that there is an effect of milieu therapy on social skills on clients I and clients II, characterized by clients following orders, the ability to maintain conversations. Discussion: There is an increase in social skills in dementia patients after being given milieu therapy.